Provincial city or regional capital? Concepts and barriers to the rebuilding of Wrocław in 1945–1947 from wartime destruction - Głowiński, Tomasz (Uniwersytet Wrocławski Wydział Nauk Historycznych i Pedagogicznych. Instytut Historyczny, 2019)
The destruction suffered by Wrocław as a result of warfare in 1945 threatened the further existence of the city, which from May of that year constituted the largest urbanised area of the western and northern lands ceded to Poland by the Allies. The main challenge faced by the Polish administration in the capital of Lower Silesia in the first period of its functioning, i.e. between 1945 and 1947, was to make an inventory of losses in the urban substance, develop a reconstruction concept for the city and begin its implementation.
Keywords: Wrocław